Violência entre parceiros íntimos: características comportamentais do agressor em situação de cárcere - Schneider, Andgélica Mirithua (2014)
The intimate partner violence is a form of abuse that affects couples and families from all over the world. The perpetrator of intimate relationship is the social actor in vogue that is part of that family system and require specialized care as much as the victim and family. Thus, this study aimed to describe the behavioral characteristics of the perpetrator of intimate relationship. Analyze categories that can be correlated with their violent behavior, such as family relations, gender relations, empathic behavior, use of licit / illicit drugs and perceptions of aggressive behavior. The sample consisted of 15 offenders arrested in the House of Detention in Curitiba. The age of participants was 23 to 50 years, with an average age of 33.53% with (sd = 9.27). The percentage of the main types of aggression issued against a partner was 23 (82.14%) including psychological aggression moral aggression, followed by physical assault including attacks against consummated or not consummated life was 18 (64.28%) and the third highlighted, sexual assault in 4 (14.28%) cases. Regarding the relationship to the victim, most offenders 11 (73.34%) were legally married or cohabiting partner of. Participants answered an interview referring to the categories mentioned and application of specialized test on emotional control. A statistical analysis of the overall results of the categories, through calculation of correlation and qualitative analysis of the interviews, which resulted in the description of each category was performed. The results showed that each category to a greater or lesser degree had correlation with aggressive behavior of the offender, such as: gender relations moderate correlation (facilitator / aggravating); family relationships strong correlation (determinant); use licit / illicit drugs strong correlation (trigger); empathic behavior very strong correlation (determining and aggravating), and perception of aggressive behavior moderate correlation (aggravating). A description of each category presented characteristics that have implications to the phenomenon of violence.